Runoff irregularities, trends, and variations in tropical semi-arid river catchment - Umar, Da’u Abba; Ramli, Mohammad Firuz; Aris, Ahmad Zaharin; Jamil, Nor Rohaizah; Abdul kareem, Jabir Haruna (Elsevier, 2018)
Study region: Hadejia River Basin (HRB) in North Eastern Nigeria. Study focus: The hydrological trends and variations of surface runoff in Hadejia river catchment were assessed using data spanning 36 years (1980–2015) for proper planning and management of water resources in the basin. New hydrological insight for the region: The temporal and spatial irregularities in the runoff of Hadeia river catchment has been detected. A significant decrease of river discharge from two out of the three downstream stations had been observed. However, there is an increasing trend of the river discharge from all the three upstream stations, though statistically insignificant. The ANOVA [F (5,210) = 106.226, P < 0.05] and cluster analysis results showed significant spatial variations between the upstream and downstream stations. The increasing trend of the discharge in the upstream stations is attributable to high rainfall mean and increased urbanization in the area. However, the significant decreasing trend of the discharge downstream of the river catchment is associated to many factors, notably; high evaporation rate due to high temperature, low rainfall mean and the relatively high infiltration rate encouraged by the high percentage of sandy soil and the sedimentary geological formation. Consequent to these trends and variations, water supply and irrigation, particularly in the downstream areas are at risk. Thus, integrated basin study using hydrological modelling will be helpful to distinguish the individual impact of the blame factors and to predict the river discharge behavior in response to the impact of those factors.